Characterization of the composition and structure of the epigeal fauna in coffee and eucalyptus monocultures, in the North of Espírito Santo (Research, Society and Development, 2021)
The aim of this study was to characterize and compare the abundance and diversity of epigeal fauna between different agricultural systems, in the municipality of Sooretama, ES. Two areas were selected: monoculture of coffee (Coffea conephora) and eucalyptus (Eucalyptus citriodora), both with 5 years old. The sampling of the epigeal fauna was carried out using pittfall traps. In each area, were installed 10 traps, which remained in the field for 7 days. After identification and quantification, were determined the number of organisms per traps per day, the total and average richness, and the Shannon diversity, Pielou uniformity and Simpson dominance indexes. The taxonomic groups also were classified according to functionality. In the coffee monoculture, the group with the highest activity was Isopoda (52.41 %), followed by the Formicidae groupd (18.46 %). In the eucalyptus plantation, the taxonomic group with the highest activity was Formicidae with 83.34 %. The planting of coffee favoured the activity and diversity of the epigean fauna, with the higher individual’s abundance, richness, and diversity than the eucalyptus monoculture. The analysis of the functionality showed that the coffee monoculture promoted better conditions for activity of the Saprophagous group (Isopoda) and the eucalyptus planting for the Social group (Formicidae).